Sistem Informasi Pendanaan Proyek Berbasis Web Pada Perusahaan Jasa Konstruksi - Magdalena, Hilyah; Santoso, Hadi; Leonita, Litha (Jurnal Transformatika, 2022)
CV. YustiKarya as a construction company realizes that the ability to manage project finance is one of the important requirements for smooth project management. CV. YustiKarya often has to manage several projects simultaneously with remote locations. This condition made it difficult for financial staff in the office to manage project financial allocations and also made it difficult for project managers in the field and had to report the status of project expenditures to the office. This difficulty drives CV. YustiKarya is to improve the project's financial management system which originally used a spread sheet to become a web-based information system. Web-based information systems will be developed using object-oriented methods. The object-oriented system development method was chosen because of its modular development capabilities and adapts to system requirements. The information system that is produced is able to create a construction project management system starting from employer entry, contract entry, billing entry, printing proof of receipt, printing proof of expenditure, and generating project income and expenditure reports online. Web-based information systems will automate the financial status of projects whose locations are scattered. This system also makes it easy for directors to be aware of current project developments.
Keywords: projects; web-based systems; object-oriented methods